2019
DOI: 10.1007/s41024-019-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of service-life prediction model for reinforced concrete structures in chloride-laden environments

Abstract: Reinforced concrete structures are subjected to several degradation processes that often occur early, especially due to reinforcements corrosion. Therefore, the use of representative models for an accurate service-life prediction of reinforced concrete structures becomes indispensable. Thus, this study is aimed at evaluating the model proposed by Andrade to efficiently predict the chloride penetration in concrete structures. In addition, the input variables of this model, as well as the challenges in obtaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…These complications can be traced to the fact that degradation mechanism often depends on numerous factors capable of affecting the process in a synergistic way; moreover, the governing failure mode may vary for different environments. Furthermore, the slow pace of degradation makes accelerated tests difficult and the large number of degradation agents make comparison with actual in-use degradation environment complicated (Martin, Saunders, Floyd, and Wineburg 1994;Marteinsson, 2005;Silvestro, Andrade, and Dal-Molin, 2019).…”
Section: Service Life and Accelerated Aging Testmentioning
confidence: 99%
“…These complications can be traced to the fact that degradation mechanism often depends on numerous factors capable of affecting the process in a synergistic way; moreover, the governing failure mode may vary for different environments. Furthermore, the slow pace of degradation makes accelerated tests difficult and the large number of degradation agents make comparison with actual in-use degradation environment complicated (Martin, Saunders, Floyd, and Wineburg 1994;Marteinsson, 2005;Silvestro, Andrade, and Dal-Molin, 2019).…”
Section: Service Life and Accelerated Aging Testmentioning
confidence: 99%
“…In previous studies on chloride diffusion, different types of marine zone have been found to be related to chloride diffusion. Some studies modeled study in environment type: underwater area [5]; tidal area [7] [15]; splash area [32]; atmospheric area or airborne salt [2] [3] [33] [34]; tidal, submerge, atmospheric [22]; tidal area, splash area, atmospheric area [28] [35]; underwater area/submerge, tidal area, splash area, atmospheric area [19] [31] [36]; dry/fully/partially saturated condition (DCC/PSC/FSC) [29].…”
Section: Classification Of Various Type Of Marine Zone and Influencing Factors Of Concretementioning
confidence: 99%
“…] -diameter of steel reinforcement [15] -water absorption [20] -mechanical load [19] -reliability index [28] -marine zone (in section 3.3) -bulk electrical resistivity [10] [25] -age of concrete [6] [17] [31], age factor [28] -effect of cations [11] -collect experimental data from other researchers/ literatures [17] [33] [34] -a visual inspection of the structure to determine the structure's current condition and the nature of testing required. [36] -location of element [36] -the properties of the corrosion inhibitor [18] [25]; -de-icing salt [24] -air content [15] [25] -coated concrete structures (double-layered systems) [37]; hollow cylinder (six-layer cylinder) [4] -the result of RCPT [6] [10] [13] [16]…”
Section: Independent Variables Dependent Variablesmentioning
confidence: 99%
“…Although, with the proposal of the new structure and the emergence of new building materials, there will be many new structural forms in the future, but it is certain that the reinforced concrete structure is still one of the most commonly used structures in the new century. However, concrete structures gradually become old, damage, or even destroy under long-term natural environment and use, affecting structural functions and safety of structural materials, so structural durability is one of the important connotations of engineering structure [3]. About relevant statistics at home and abroad showed that economic losses caused by the durability of concrete structures, and as the environmental changes and functional requirements occur, durability problems were getting more and more prominent.…”
Section: Introductionmentioning
confidence: 99%